Process Improvement of Claims Handling in Insurance Industry - Abdullaeva, Nadiia; Martínez, Felipe; Jirsák, Petr; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2019)
This master thesis focuses on the optimization of the claim handling process in the insurance industry. The research can be considered as a replicable roadmap for the insurance companies to improve their processes of the claim settlement. Based on the literature review, quantitative data obtained from the insurance company and the qualitative data gathered from the interviews, this thesis identifies key opportunities for improvement in the insurance industry with application of DMAIC methodology. The author analyses the main challenges occurring in the process to identify their roots and causes. Once the reasons of the challenges identified, the author develops the improvement proposal to improve three Kaizen events. Such improvement proposal would decrease the claim settlement time from 39 to 25 days and reduce the number of errors by 19%. To sustain the current level of process performance, the author offers various control tools, which can enable to keep the results of implemented projects for the long-term period.
Vedoucí práce: Felipe Martínez
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses